Women on poetry writing, revising, publishing and teaching - Smallwood, Carol, 1939-; Harris, Colleen S., 1979-; Brackett-Vincent, Cynthia (McFarland & Co., 2012)
"This collection of 59 essays captures the wit and wisdom of published contemporary female poets, who reveal their victories and struggles with writing. Topics include the collective writing life, tips on teaching in numerous contexts, the publishing process, and general advice to aid the poet in her chosen vocation. Includes a foreword by noted poet, Molly Peacock"--Provided by publisher.